Dual Time-Point 18F-FDG PET/CT in Spinal Sarcoidosis: A Single Institution Case Series (2019)
Study Design.A case series of dual time-point 18F-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) for the diagnosis of spinal cord sarcoidosis.Objective.The aim of this study was to illustrate three cases of spinal sarcoidosis with occult presentation and subsequent identification with the use of dual time-point 18F-FDG PET/CT.Summary of Background Data.Sarcoidosis of the spinal cord is very rare and when it occurs without systemic manifestations of disease can be a challenging diagnostic dilemma frequently resulting in the need for spinal cord biopsy in order to establish a diagnosis.Methods.Case series presentation and report.Results.This manuscript presents a case series experience of dual time-point 18F-FDG PET/CT for the diagnosis of spinal cord sarcoidosis. We review the cases of three patients who presented with myelopathy and underwent 18F-FDG DTPI as part of the evaluation for enhancing spinal cord lesions of unknown etiology for 2 years at a university-based cancer hospital. 18F-FDG DTPI was vital in making the diagnosis of sarcoidosis, and in two of the cases, the patients were able to avoid biopsy, thereby avoiding potential morbidity from an invasive procedure.Conclusion.18F-FDG PET/CT imaging is a noninvasive imaging technique that can be crucial in the diagnosis of sarcoidosis of the spinal cord and help avoid unnecessary procedures.Level of Evidence: 4. © 2019 Wolters Kluwer Health, Inc. All rights reserved.